2006
DOI: 10.1523/jneurosci.2592-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Weakened Center-Surround Interactions in Visual Motion Processing in Schizophrenia

Abstract: Schizophrenia is often accompanied by a range of visual perception deficits, with many involving impairments in motion perception. The presence of perceptual abnormalities may impair neural processes that depend on normal visual analysis, which in turn may affect overall functioning in dynamic visual environments. Here, we examine the integrity of suppressive center-surround mechanisms in motion perception of schizophrenic patients. Center-surround suppression has been implicated in a range of visual functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

28
178
6
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(213 citation statements)
references
References 88 publications
(111 reference statements)
28
178
6
1
Order By: Relevance
“…Studies in aging found age-associated decreases in GABA mediated inhibition [17] and reduced surround suppression on motion perception [18]. The increased surround suppression, found in this study, and the reduced surround suppression, found in a previous study, in schizophrenia suggest that abnormalities in inhibitory control of motion processing are multi-faceted in nature [14,19].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Studies in aging found age-associated decreases in GABA mediated inhibition [17] and reduced surround suppression on motion perception [18]. The increased surround suppression, found in this study, and the reduced surround suppression, found in a previous study, in schizophrenia suggest that abnormalities in inhibitory control of motion processing are multi-faceted in nature [14,19].…”
Section: Discussionsupporting
confidence: 69%
“…The dependence of surround modulation on signal strength is analogous to the finding that center-surround interaction in schizophrenia is weakened for high contrast stimuli [14]. Both results suggest that suppressive surround modulation is abnormal in schizophrenia when salient motion stimuli (such as those with high contrast or intermediate motion coherence) adequately activate the neural circuitry.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…For instance, it has been reported that surround suppression mechanisms in old people and patients with schizophrenia are weak. At the same time, they experience difficulties in segregating figure from background (Betts et al 2005;Tadin et al 2006), a finding that underlies the importance of surround mechanisms.…”
Section: Discussionmentioning
confidence: 99%